Infrastructure of Secondary Schools in The Context of Using New Technologies in Education - Małgorzata KOSAŁA; Małgorzata ZAKRZEWSKA; Aleksandra BORKOWSKA (Communications of International Proceedings, 2022)
The paper concerns the assessment of the infrastructure of secondary schools in the context of distance learning and students' attitude to undertaking remote work in the future. The aim of the paper is to discuss the results of empirical research conducted among secondary school students from Poland. The presented results refer to the research questions posed: RQ1: Are Polish secondary schools well equipped in digital technology such as computers or Wi-Fi?; RQ2: Is the situation of digital technology used in technical secondary schools worse than in general secondary schools?
Keywords: Education; New technologies; Infrastructure; Secondary school